Functional and Structural Changes of the Blood-Nerve-Barrier in Diabetic Neuropathy - Richner, Mette; Ferreira, Nelson; Dudele, Anete; Jensen, Troels S.; Vaegter, Christian B.; Gonçalves, Nádia P. (Frontiers in Neuroscience, 2019)
The incidence of diabetes mellitus is approaching global epidemic proportions and should be considered a major health-care problem of modern societies in the twenty-first century. Diabetic neuropathy is a common chronic complication of diabetes and, although an adequate glycemic control can reduce the frequency of diabetic neuropathy in type 1 diabetes, the majority of type 2 diabetic patients will develop this complication. The underlying cellular and molecular mechanisms are still poorly understood, preventing the development of effective treatment strategies. However, accumulating evidence suggests that breakdown of the blood-nerve barrier (BNB) plays a pivotal pathophysiological role in diabetic neuropathy. In the present review, we highlight the structural and functional significance of the BNB in health and disease, focusing on the pathological molecular events leading to BNB dysfunction in diabetic neuropathy. In addition, we discuss potential molecular targets involved in BNB homeostasis that may pave the way towards novel therapeutic strategies for treating diabetic neuropathy.